2021
DOI: 10.1101/2021.04.04.438369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybridization and the Coexistence of Species

Abstract: It is thought that two species can coexist if they use different resources present in the environment, yet this assumes that species are completely reproductively isolated. Closely related species often interbreed, raising the question of how this might affect coexistence. We model coexistence outcomes for two sympatric species that are ecologically differentiated but have incomplete reproductive isolation. Results show that the consequences of interbreeding depend crucially on hybrid fitness. When hybrid fitn… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…2012). Conversely, even a very small amount of hybridization or just interbreeding itself between lineages with strong assortative mating could suffice to prevent coexistence (Irwin and Schluter 2022). However, if neither ecology, sexual selection, nor their interaction suffices to complete reproductive isolation, competing species may stay in stable parapatry at contact zones (Tobias et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2012). Conversely, even a very small amount of hybridization or just interbreeding itself between lineages with strong assortative mating could suffice to prevent coexistence (Irwin and Schluter 2022). However, if neither ecology, sexual selection, nor their interaction suffices to complete reproductive isolation, competing species may stay in stable parapatry at contact zones (Tobias et al.…”
Section: Discussionmentioning
confidence: 99%
“…2020; but see M'Gonigle et al. 2012) or when hybridization occurs even under high assortative mating (Irwin and Schluter 2022). As such, secondary contact zones may differ from one another in where they could be placed within the “gray zone” of late‐stage speciation (Roux et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological divergence can mediate premating reproductive isolation by limiting how often individuals of different populations meet. Furthermore, phenotypic divergence resulting from adaptation to different environments (e.g., ecomorphology) can indirectly result in postzygotic isolation by rendering phenotypically intermediate hybrids unfit (Irwin & Schluter, 2022; Schluter, 2009). Ecomorphology is, in general, quite conservative within the H. planiceps complex, with the exception of larger body size in limestone‐restricted lineages; but whether this reflects drift within isolates or habitat‐induced adaptation is unclear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, they also showed that extinction can be avoided by producing a hybrid swarm when hybrid fitness is high. While our model assumes that there are only two outcomes in reproductive character displacement (i.e., extinction or coexistence), we need to carefully consider the three possibilities (i.e., extinction, coexistence or hybridization) for understanding the eco-evolutionary dynamics of speciation by reinforcement/reproductive character displacement (Irwin & Schluter, 2021;Kyogoku & Kokko, 2020).…”
Section: Discussionmentioning
confidence: 99%